Building User Interfaces by Direct Manipulation - Cardelli, Luca (ACM Symposium on User Interface Software and Technology, 1988)
User interfaces based on mice, bitmap displays and windows are becoming commonplace, and there are guidelines on how such interfaces should function [Apple 85]. As a consequence, there is a growing expectation that all programs, no matter how trivial or how complicated, should present a graphically elegant and sophisticated user interface.